Heightened incidence of adverse events associated with a live attenuated varicella vaccine strain that lacks critical genetic polymorphisms in open reading frame 62 - Kim, Ye Ji; Oh, Doyeop; Kim, Jaehoon; Son, Jeongtae; Moon, Jae Yun; Kim, Ye Kyung; Ahn, Bin; Kang, Kyu Ri; Park, Daechan; Kang, Hyun Mi (Clinical Microbiology and Infection, 2024)
Objectives: This study aimed to identify the specific vaccine strain associated with herpes zoster (HZ) in children following a series of diagnosed cases and to explore whether differences in single nucleotide polymorphisms (SNPs) among various vaccine strains are linked to an increased incidence of herpes zoster after vaccination. Methods: From February 2021 to March 2024, children <12 years old suspected of vaccine-related varicella-like rash or HZ were included. Varicella zoster virus DNA isolated from the patients were sequenced to differentiate vaccine type versus wild-type. 3D protein structures of pORF62 were simulated using open reading frame 62 sequences extracted from whole genome sequencing of vOka, MAV/06, Oka/SK vaccines, and pOka reference. Results: A total of 27 children with a median age of 2.1 (interquartile range, 1.5–3.4) years old presented with vaccine-related varicella-like rash (n = 4/27, 14.8%) or HZ (n = 23/27, 85.2%). One patient with varicella-like rash and 34.8% (n = 8/23) with HZ had disseminated skin involvement. All were immunized with the Oka/SK strain varicella vaccine. Genotyping showed 88.2% (n = 15/17) had SNPs specific to the Oka/SK strain, and two had SNPs considered pOka type contained within the Oka/SK vaccine. Despite accumulations of SNPs in ORF 62 of Oka/SK, the translated amino acid sequence and 3D protein structure were identical to wild-type pOka's pORF62. In vOKA and MAV/06, changes in amino acids occurred at two positions, S628G and R958G, within pORF62. The predicted 3D protein structure of vOka and MAV/06's pORF62 showed that the α helical structure within region I undergoes conformational change, potentially increasing difficulties in interactions with infection-related proteins and thereby decreasing virulence. pORF62 in pOka and Oka/SK exhibited more stable structure complex of the α helical structure. Discussion: Lack of structural alternations in region I of pORF62 due to the absence of critical genetic polymorphisms in open reading frame 62 could be associated with the heightened incidence of adverse events.
Keywords: Chickenpox Vaccine; Child; Child, Preschool; DNA, Viral; Female; Herpes Zoster; Herpesvirus 3, Human; Humans; Incidence; Infant; Male; Open Reading Frames; Polymorphism, Single Nucleotide; Vaccines, Attenuated; Adverse events; Attenuation; Herpes zoster; Vaccine; Varicella zoster